Optimization of Time Management Based on Islamic Teachings and Values in the ROHIS Work Program at SMAN 1 Leuwidamar - Alsri Nurcahya; Ohib Muhibburrohman; Aspandi; Machdum Bachtiar (al-Afkar, Journal For Islamic Studies, 2024)
SMA Negeri 1 Leuwidamar has a student affairs program, including the extracurricular activity of Islamic Spirituality (ROHIS), aimed at enhancing the students religiosity through a work program based on Islamic teachings. Recognizing the significance of effective and efficient time management, particularly guided by Islamic teachings, is key to the success of implementing the ROHIS work program at the school. The objective of this research is to analyze the optimization of time management based on Islamic teachings in the ROHIS work program at SMA Negeri 1 Leuwidamar. This study adopts a qualitative research method, specifically analyzing the concept of time management based on Islamic teachings in the ROHIS Work Program at SMA Negeri 1 Leuwidamar. Data is obtained through direct observation and interviews with ROHIS mentors and officials. The study employs the perspectives of the Quran and Hadith to analyze time management based on Islamic teachings in the ROHIS work program at SMA Negeri 1 Leuwidamar. The findings indicate that optimizing time management based on Islamic values in the ROHIS work program adds deeper meaning and aligns with the principles desired by Islam, enabling ROHIS to play a more effective role in shaping a characteristically Islamic generation that contributes positively to society.